Diabetes Mellitus Among Pulmonary Tuberculosis Patients From 4 Tuberculosis-endemic Countries: The TANDEM Study. (8th April 2019) - Ugarte-Gil, Cesar; Alisjahbana, Bachti; Ronacher, Katharina; Riza, Anca Lelia; Koesoemadinata, Raspati C; Malherbe, Stephanus T; Cioboata, Ramona; Llontop, Juan Carlos; Kleynhans, Leanie; Lopez, Sonia; Santoso, Prayudi; Marius, Ciontea; et al.
Abstract: Background: Diabetes mellitus (DM) increases active tuberculosis (TB) risk and worsens TB outcomes, jeopardizing TB control especially in TB-endemic countries with rising DM prevalence rates. We assessed DM status and clinical correlates in TB patients across settings in Indonesia, Peru, Romania, and South Africa. Methods: Age-adjusted DM prevalence was estimated using laboratory glycated hemoglobin (HbA1c) or fasting plasma glucose in TB patients. Detailed and standardized sociodemographic, anthropometric, and clinical measurements were made. Characteristics of TB patients with or without DM were compared using multilevel mixed-effect regression models with robust standard errors. Results: Of 2185 TB patients (median age 36.6 years, 61.2% male, 3.8% human immunodeficiency virus–infected), 12.5% (267/2128) had DM, one third of whom were newly diagnosed. Age-standardized DM prevalence ranged from 10.9% (South Africa) to 19.7% (Indonesia). Median HbA1c in TB–DM patients ranged from 7.4% (Romania) to 11.3% (Indonesia). Compared to those without DM, TB–DM patients were older and had a higher body mass index (BMI) ( P value < .05). Compared to those with newly diagnosed DM, TB patients with diagnosed DM had higher BMI and HbA1c, less severe TB, and more frequent comorbidities, DM complications, and hypertension ( P value < .05). Conclusions: We show that DM prevalence and clinical characteristics of TB–DM vary across settings. Diabetes is primarily known but untreated, hyperglycemia is often severe, and many patients with TB–DM have significant cardiovascular disease risk and severe TB. This underlines the need to improve strategies for better clinical management of combined TB and DM. Abstract : Prevalence and characteristics of diabetes mellitus (DM) in Tuberculosis (TB) patients varies between countries underlining the need for setting specific data. DM amongst TB patients was mostly diagnosed but poorly controlled. Those with TB-DM had increased comorbidities, DM complications and raised Cardiovascular disease (CVD) risk.